Review and Reconstruction of M.Ed. Curriculum in different Universities A Study - Yadav, S.K. (INDIAN EDUCATIONAL REVIEW, 2016)
The quality of teachers depends upon the quality of teacher-educators who are the product of the Master in Education (M.Ed.) programme of teacher education. The quality of teacher-educators depends on M.Ed. curriculum and its transaction. In this regard, the policy documents have also made several recommendations from time to time for improving the quality of curriculum, content and course structure of Master in Education (M.Ed.) programme. National Curriculum Framework for Teacher Education (NCFTE) –2009 suggested innovative curriculum and course of M.Ed. programme for its quality improvement. The present study examined the status of M.Ed. (General) and M.Ed. (Special Education) curricula run in twenty-eight Central and State Universities in terms of course structure, accrediting agencies, working days, practicum, research component, examination and evaluation, weightage assigned to core and optional theory papers etc. The extent to which the curricula of M.Ed. programme run in these universities are in consonance with NCFTE, 2009 and as per revised norms and standards of National Council of Teacher Education (NCTE) Regulations–2014 have been discussed in this paper.